To QE or Not to QE? The Japanese Experience - Radu Lupu; Adrian Cantemir Calin (Hyperion Economic Journal, 2014)
This paper studies the effect of a series of quantitative easing initiatives belonging to the Bank of Japan on Central and Eastern European sovereign CDSs. Using daily data for the 2005 – 2013 period and considering 23 announcements of QE initiatives we build an econometric event study approach in order to compute and investigate the abnormal returns induced by these announcements. The results indicate a strong effect of the Japanese QE policies on the CEE sovereign Credit Default Swaps.